International multicentre review of perioperative management and outcome for catecholamine‐producing tumours. Issue 2 (5th January 2020) - Groeben, H.; Walz, M. K.; Nottebaum, B. J.; Alesina, P. F.; Greenwald, A.; Schumann, R.; Hollmann, M. W.; Schwarte, L.; Behrends, M.; Rössel, T.; Groeben, C.; Schäfer, M.; et al.
Abstract : Background: Surgery for catecholamine‐producing tumours can be complicated by intraoperative and postoperative haemodynamic instability. Several perioperative management strategies have emerged but none has been evaluated in randomized trials. To assess this issue, contemporary perioperative management and outcome data from 21 centres were collected. Methods: Twenty‐one centres contributed outcome data from patients who had surgery for phaeochromocytoma and paraganglioma between 2000 and 2017. The data included the number of patients with and without α‐receptor blockade, surgical and anaesthetic techniques, complications and perioperative mortality. Results: Across all centres, data were reported on 1860 patients with phaeochromocytoma or paraganglioma, of whom 343 underwent surgery without α‐receptor blockade. The majority of operations (78·9 per cent) were performed using minimally invasive techniques, including 16·1 per cent adrenal cortex‐sparing procedures. The cardiovascular complication rate was 5·0 per cent overall: 5·9 per cent (90 of 1517) in patients with preoperative α‐receptor blockade and 0·9 per cent (3 of 343) among patients without α‐receptor blockade. The mortality rate was 0·5 per cent overall (9 of 1860): 0·5 per cent (8 of 517) in pretreated and 0·3 per cent (1 of 343) in non‐pretreated patients. Conclusion: There is substantial variability in the perioperative management of catecholamine‐producing tumours, yet the overall complication rate is low. Further studies are needed to better define the optimal management approach, and reappraisal of international perioperative guidelines appears desirable. Abstract : Morbidity and mortality rates are difficult to determine in rare diseases like phaeochromocytoma. To date there has been no randomized study of the perioperative management of these patients. Therefore, an international and interdisciplinary effort was made to provide a broad overview of the current management of phaeochromocytoma. Adverse effects frequent with preoperative blocking Abstract : Antecedentes: La cirugía de los tumores productores de catecolaminas puede complicarse por la inestabilidad hemodinámica intraoperatoria y postoperatoria. Se han propuesto distintas estrategias de manejo perioperatorio, pero ninguna ha sido evaluada en ensayos aleatorizados. Para evaluar este tema, se han recogido los datos de los resultados y del manejo perioperatorio contemporáneo de 21 centros. Métodos: Veintiún centros aportaron datos de los resultados de los pacientes operados por feocromocitoma y paraganglioma entre 2000‐2017. Los datos incluyeron el número de pacientes con y sin bloqueo del receptor α, las técnicas quirúrgicas y anestésicas, las complicaciones y la mortalidad perioperatoria. Resultados: Los centros en su conjunto aportaron datos de 1.860 pacientes con feocromocitoma y paraganglioma, de los cuales 343 pacientes fueron intervenidos sin bloqueo del receptor α. La gran mayoría (79%) de las cirugías se realizaron utilizando técnicas mínimamente invasivas, incluido un 17% de procedimientos con preservación de la corteza suprarrenal. La tasa de complicaciones cardiovasculares fue de 5, 0% en total; 5, 9% (90/1517) en pacientes con bloqueo preoperatorio de los receptores α y 0, 9% (3/343) en pacientes no pretratados. La mortalidad global fue del 0, 5% (9/1860); 0, 5% (8/1517) en pacientes pretratados y 0, 3% (1/343) en pacientes no tratados previamente. Conclusión: Existe una variabilidad sustancial en el manejo perioperatorio de los tumores productores de catecolaminas, aunque la tasa global de complicaciones es baja. Este estudio brinda la oportunidad para efectuar comparaciones sistemáticas entre estrategias de prácticas terapéuticas variables. Se necesitan más estudios para definir mejor el enfoque de manejo óptimo y parece conveniente volver a evaluar las guías internacionales perioperatorias.